PENYULUHAN DAN PEMERIKSAAN IVA TES PADA KOMUNITAS PARALEGAL WILAYAH MORODEMAK DAN GUNTUR, DEMAK - Dian Nintyasari Mustika; Siti Istiana; Fitriani Nur Damayanti; Lia Mulyanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Background: Cervical cancer or commonly known as cervical cancer is one of the biggest causes of death for women, at least every year worldwide more than 270,000 deaths occurred due to cervical cancer. IVA test examination is an examination of alternative screening pap smear because it is cheaper, practical, very easy to implement and simple equipment and can be done by health personnel such as midwives in addition to obstetricians gynecology. Destination: Conduct reproductive health services for women. Methods: Descriptive by describing the course of the process of community service. Results: Community paralegals IVA test examination were 44 respondents. This examination was conducted over two days on July 30 and August 6, 2015. The age of respondents who follow IVA test that is 11.4% of 20-29 years, 30-39 years 34%, 40-49 years 27.3%, 50-59 years 25%, 60-69 years 2.3%. The use of condoms contraception 2.3%, 2.3% pills, injections 3 months 27.3%, IUD 4.5%, 9.1% Implant, MOW 15.9%, 38.6% and without planning. IVA examination results that from 44 respondents, 4 respondents with positive results IVA, and 40 respondents negatively. Then the results obtained inspekulo 26 respondents experienced erosion and 18 respondents did not experience erosion.Keywords: IVA Test, Paralegal